1996
DOI: 10.1111/j.1467-9299.1996.tb00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing Local Government? Some Evidence Assessed

Abstract: Osborne and Gaebler's Reinventing Government offers a powerful image of a revolution in government. This article explores some of the assumptions of that seminal work as they relate to the nature of the change process. Parallels are drawn with the debate on the nineteenth‐century revolution in government, and Osborne and Gaebler's work is judged unlikely to survive the critical perspective of history. Their work may nonetheless be taken as providing a research agenda for the study of the recent extensive chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…they believe it has resulted in net savings locally (73%) and nationally (69%). This is a much larger proportion, and a statistically significant difference, than that reported by the LGMB (1996) survey of 205 local authority chief executives which reported that, in 1994, 57 per cent believed that competition had reduced the costs of service provision (see also Young 1996).…”
Section: Research Findings: Blue Collar Cctmentioning
confidence: 75%
“…they believe it has resulted in net savings locally (73%) and nationally (69%). This is a much larger proportion, and a statistically significant difference, than that reported by the LGMB (1996) survey of 205 local authority chief executives which reported that, in 1994, 57 per cent believed that competition had reduced the costs of service provision (see also Young 1996).…”
Section: Research Findings: Blue Collar Cctmentioning
confidence: 75%
“…More than two-thirds of authorities have adapted their decision-making structures over the last seven years. There have also been considerable shifts in councillors' awareness of the need to change from formal to less formal structures over this period (Young 1996(Young , 1998.…”
Section: Patterns Of Changementioning
confidence: 99%
“…Local government has not ossified in the years since it lost the battle to control health service activity. In particular, it has moved away from its providing roots towards the entrepreneurial model outlined by Osborne and Gaebler in their influential book Reinventing Government (Osborne and Gaebler 1992;Young 1996). This model is set out as a set of linked approaches: which empowers people rather than merely serving them; which operates under the discipline of competition; which is mission rather than rule-driven; which is results-oriented, stressing outcomes from, rather than inputs to, the policy process; which is oriented to the needs of the customer; which is concerned to generate money rather than spend it; which is forward-looking and operates through decentralized structures with flat hierarchies; and which works to lever change through market processes.…”
Section: The Changing Nature Of Local Governmentmentioning
confidence: 99%
“…Although Young (1996) argues that not all of these precepts are evident in every case, there is nevertheless strong evidence that local government is undergoing a process of radical change, particularly around the use of the quasi-market and contracts, as an alternative to the traditional "command and control" approach where both planning and service delivery are part of the same structure. Blackman (1995), for example, argues that the failure of bureaucratic control to enable managers to extricate themselves from operational issues and undertake strategic planning and evaluation means that it is unlikely that separate planning and provision functions will be conflated again.…”
Section: The Changing Nature Of Local Governmentmentioning
confidence: 99%